Devolatilization of subducting slabs, part II: volatile fluxes and storage - Tian, M; Katz, R; Rees Jones, D; May, D (American Geophysical Union, 2019)
Subduction is a crucial part of the long‐term water and carbon cycling between Earth's exosphere and interior. However, there is broad disagreement over how much water and carbon is liberated from subducting slabs to the mantle wedge and transported to island‐arc volcanoes. In the companion paper Part I, we parameterize the metamorphic reactions involving H2O and CO2 for representative subducting lithologies. On this basis, a two‐dimensional reactive transport model is constructed in this Part II. We assess the various controlling factors of CO2 and H2O release from subducting slabs. Model results show that up‐slab fluid flow directions produce a flux peak of CO2 and H2O at subarc depths. Moreover, infiltration of H2O‐rich fluids sourced from hydrated slab mantle enhances decarbonation or carbonation at lithological interfaces, increases slab surface fluxes, and redistributes CO2 from basalt and gabbro layers to the overlying sedimentary layer. As a result, removal of the cap sediments (by diapirism or off‐scraping) leads to elevated slab surface CO2 and H2O fluxes. The modelled subduction efficiency (the percentage of initially subducted volatiles retained until ~200 km deep) of H2O and CO2 is increased by open‐system effects due to fractionation within the interior of lithological layers.